Can [125I]-Iodocyanopindolol Label β3-Adrenoceptors in Rat Urinary Bladder? - Schneider, Tim; Michel, Martin C. (Frontiers in Pharmacology, 2010)
β3-Adrenoceptors have been demonstrated to mediate urinary bladder smooth muscle relaxation but proof of their expression at the protein level has been missing because of lack of suitable antibodies or radioligands. As among various available radioligands [125I]-iodocyanopindolol ([125I]-ICYP) exhibited the smallest problems in labelling cloned human β3-adrenoceptors in previous studies, we have explored its suitability to label β3-adrenoceptors in rat urinary bladder in saturation and competition radioligand binding experiments. Rat lung was used as an internal control and exhibited all characteristics expected from this tissue with regard to β1/β2-adrenoceptor labelling. Saturation and competition binding studies with [125I]-ICYP in rat bladder yielded saturable binding sites with an affinity compatible with β3-adrenoceptors. In competition experiments various agonists and antagonists largely exhibited a profile compatible with a population consisting largely of β3-adrenoceptors. However, the binding competition properties of ICI 118,551 and SR 59,230A were not easily explained by the idea of labelling a homogeneous β3-adrenoceptor population but interpretation of the data was limited by a high degree of non-specific binding in [125I]-ICYP concentrations required to label the receptors. We conclude that [125I]-ICYP can be used to label tissue β3-adrenoceptors but results obtained with this ligand have to be interpreted with caution.